Pemetaan Penderita Pneumonia di Surabaya dengan Menggunakan Geostatistik - Stefanie Hartanto; Siana Halim; Oviliani Yenty Yuliana (Institute of Research and Community Outreach - Petra Christian University, 2010)
In this paper we mapped the location of Pneumonia disease in Surabaya. We also analyse the survival of the afflicted and predict the spread of the disease using Kriging. The study reveals that after 45 days in the hospital, the survival of the Pneumonia’s patients decrease to 46.8%. Moreover, the centers of this disease are in Tubanan and Sukomanunggal Both of these regions are in West Surabaya which also is an industrial part of the city.